1969
DOI: 10.2183/pjab1945.45.507
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Observation of Endothelial Surface of Heart and Blood Vessels

Abstract: The introduction of the scanning electron microscope into biological research has revolutionized the possibilities of studying the surface structures of biological specimens. The method was used originally for the surface of hard tissue ; however, the improved fixation method, which preserves quite well the ultrastructure of soft tissues as shown by Barber and Boyde (1968) ,1) has now made it possible to observe the fine structure of the surface of soft tissues.The present investigation is a study of the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

1972
1972
1976
1976

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 1 publication
2
14
1
Order By: Relevance
“…2a). These observations are consistent with already published scanning electron-microscopical find ings [6] about the inner surface of freshly prepared venous material. Ac cording to these observations, the smaller extensions of the longitudinal prominences may represent endothelial processes ( fig.…”
Section: Luminal Venous Surfacesupporting
confidence: 93%
See 1 more Smart Citation
“…2a). These observations are consistent with already published scanning electron-microscopical find ings [6] about the inner surface of freshly prepared venous material. Ac cording to these observations, the smaller extensions of the longitudinal prominences may represent endothelial processes ( fig.…”
Section: Luminal Venous Surfacesupporting
confidence: 93%
“…A folded and wrin kled profile of the luminal surface has already been observed in larger vessels by scanning electron-microscopical studies. It is particularly prominent in arteries [4] but also clearly visible in veins [6] and is evi dently formed by the internal elastic membrane. The integrity of the en dothelial layer is certainly a most important indication, whether the prep aration of the lyophilized material was of optimal quality or not.…”
Section: Discussionmentioning
confidence: 99%
“…2), as described by Garbarsch and Christensen 9 with silver nitrate staining. "Bridge-like structures" such as those described by Shimamoto et al 10 and Sunaga et al 11 were sometimes observed in tissues from control animals. They were also present in the area which had been compressed by the clip (fig.…”
Section: Sem Of the Ischemic C O M M O N Carotid Arterymentioning
confidence: 82%
“…The endothelial surface structure of the heart has been studied by scanning electron microscopy (SEM) by a few research groups (SHIMAMOTO, YAMASHITA and SUNAGA, 1969;MAGUIRE, 1972;WHEELER, GAVIN and HERDSON, 1973;BUSS, DAHM and LINDENFELSER, 1973;TOKUNAGA, OSAKA and FUJITA, 1973). Apparently because of the strong contraction and shrinkage easily occurring during the procedures of specimen preparation, the results obtained by these authors are conspicuously divergent.…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively few papers have been published in this field of study. SHIMAMOTO, YAMASHITA and SUNAGA (1969) reported the existence of "intercellular bridges"…”
Section: Discussionmentioning
confidence: 99%